1991
DOI: 10.1016/0014-4827(91)90368-5
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial synthesis of tenascin at tips of growing bronchi and graded accumulation in basement membrane and mesenchyme

Abstract: The extracellular matrix protein, tenascin, has been proposed as mediator in epithelial-mesenchymal interactions because of its characteristic distribution during embryogenesis. Here we compared the accumulation of tenascin and laminin in the early chicken lung bud. Laminin is deposited in the basement membrane, starting at the tips and increasing along the shafts of growing primary and secondary bronchi. In contrast, tenascin accumulation is highest in basement membranes and mesenchyme at sites where new bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 23 publications
3
29
1
Order By: Relevance
“…These findings are in concordance with the results of the present study and suggest that myofibroblasts are mainly tenascin-C-synthesizing cells in RDS and BPD. In early chicken lung bud, however, tenascin-C mRNA was found to be synthesized by the epithelium, inconsistent with the results of the present study (Koch et al 1991). The IHC expression for tenascin-C within alveolar and bronchiolar walls was stronger in patients with RDS and BPD than in controls.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in concordance with the results of the present study and suggest that myofibroblasts are mainly tenascin-C-synthesizing cells in RDS and BPD. In early chicken lung bud, however, tenascin-C mRNA was found to be synthesized by the epithelium, inconsistent with the results of the present study (Koch et al 1991). The IHC expression for tenascin-C within alveolar and bronchiolar walls was stronger in patients with RDS and BPD than in controls.…”
Section: Discussioncontrasting
confidence: 99%
“…This effect could correlate with tenascin functioning both as a differentiation factor (which could inhibit cell growth) and as a mitogen. A similar contrasting pattern of cellular responses has been observed in the effects of tenascin on attachment of neural cells or outgrowth of neuritcs (Wehrle-Haller et al, 1991). Of special interest is the observation that tenascin can enhance the mitogenic action of major polypeptide growth factors such as EGF, an effect which may be relevant to some of the above-mentioned processes.…”
Section: Discussionmentioning
confidence: 55%
“…Fibroncctin was prepared from conditioned medium of chick embryo fibroblasts (Wehrle-Haller et al, 1991). The protein was eluted from a gelatine-Sepharose column with 4 M urea, 20 mM Tris/HCl pH 7.4.…”
Section: Purification Of Tenascin and Other Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown by in situ hybridization that in early lung development the epithelium at the tips of the growing bronchi is the source of the tenascin transcripts, but the protein is found quite distantly from the site of its synthesis (Koch et aL, 1991). Interestingly, Prieto et al (1990) have found that the embryonic lung epithelium contains tenascin mRNA, including the extra repeats, and thus should secrete the large tenascin variants.…”
Section: Discussionmentioning
confidence: 99%